THE FORMATION OF NOUNS IN ENGLISH AND UZBEK LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article presents a comparative analysis of noun formation in Uzbek and English languages. Nouns, being an essential part of both languages, play a crucial role in communication and linguistic expression. The study explores the various mechanisms involved in creating nouns in Uzbek and English, including derivation, compounding, and borrowing